Virulence characteristic and antibiotic susceptibility of Aeromonas salmonicida isolated from patients with gastroenteritis and urinary tract infections in Kirkuk City- Iraq - Abdulqadir , Berivan Abdulrazak; Shareef , Hajir Ali (International Journal of Medical Toxicology and Legal Medicine, 2024)
Aims: Aeromonas salmonicida is the causative agent for furunculosis, which is a superficial skin infection in fish, especially in Salmonids; hence named salmonicida. It is a rare but potential pathogen for human infection; it has been associated with cases of blood, skin, eye, endocardial, gastrointestinal, and urinary tract infections. Therefore, the present study aimed to determine the prevalence of: virulence, biofilm formation, and resistant patterns and to detect beta-lactamase enzyme production phenotypically. Methodology and results: A total of three Aeromonas isolates were included in this study. Two isolates recovered from stool samples of patients with gastroenteritis, and one isolate recovered from patients with urinary tract infections. These three isolates were identified as Aeromonas salmonicida using a GNID card in the Vitek 2 compact system. The antibiotic susceptibility testing was performed using the disc diffusion method. A double disc synergy test was applied to determine the presence of extended-spectrum B-lactamase (ESBL) production. Carbapenemase was screened using the modified Hodge test (MHT) and boronic acid test. Five virulence factors, including protease, lipase, esterase, hemolysins, and biofilm production, were studied. All three isolates exhibited multiple drug resistance patterns (MDR). ESBL and carbapenemase enzymes were seen in stool A. salmonicida isolates only. All three isolates showed multifactorial virulence factor activity. Conclusion, significance, and impact of the study: ESBL and carbapenemase-producing A. salmonicida emerged as relevant human intestinal pathogens with a variety of pathogenicity factors, so this study emphasizes on the importance of active surveillance plans to control infection and the spread of this pathogen.